Serotypes and Antibiotic Susceptibility of Streptococcus pneumoniae Isolates from Invasive Pneumococcal Disease and Asymptomatic Carriage in a Pre-vaccination Period, in Algeria - Ziane, Hanifa; Manageiro, Vera; Ferreira, Eugénia; Moura, Inês B.; Bektache, Soumia; Tazir, Mohamed; Caniça, Manuela (Frontiers in Microbiology, 2016)
In Algeria, few data is available concerning the distribution of pneumococcal serotypes and respective antibiotic resistance for the current pre-vaccination period, which is a public health concern. We identified the most frequent Streptococcus pneumoniae serogroup/types implicated in invasive pneumococcal disease (IPD) (n=80) and carriage (n=138) in Algerian children younger than 5 years old. Serogroup/types of 78 IPD isolates were identified by capsular typing using a sequential multiplex PCR. Overall, serotypes 14, 19F, 6B, 23F, 18C 1, 5, 7F, 19A and 3 (55% of PCV7 serotypes, 71.3% of PCV10 and 90% of PCV13) were identified. Additionally, 7.5% of the non-vaccine serotypes 6C, 9N/L, 20, 24F, 35B, and 35F, were observed. In the case of S. pneumoniae asymptomatic children carriers, the most common serogroup/types were 6B, 14, 19F, 23F, 4, 9V/A, 1, 19A, 6A and 3 (42.7% of PCV7 serotypes, 44.2% of PCV10 and 58% of PCV13). For 6.1% of the cases co-colonization was detected. Serotypes 14, 1, 5 and 19A were more implicated in IPD (p<0.01), whereas serotype 6A was exclusively isolated from carriers (p<0.01). Deaths associated with IPD were related to serotypes 19A, 14, 18C and one non-typeable isolate. Among IPD related to vaccine serotypes, the rates of penicillin non-susceptible isolates were higher in no meningitis cases (80%) than in meningitis (66.7%), with serotypes 14, 19A, 19F and 23F presenting the highest MIC levels (> 2μg/ml). Resistance to cefotaxime was higher in isolates from meningitis (40.5%); however, resistance to erythromycin and co-trimoxazole (> 40%) was more pronounced in no-meningeal forms. Overall, our results showed that PCV13 conjugate vaccine would cover up to 90% of the circulating isolates associated with IPD in Algeria, highlighting the importance of monitoring the frequency of S. pneumoniae serogroups/types during pre- and post-vaccination periods.